A Modification of the Sedimentation Unit with Continuous Discharges Flow (CDF) as a New Method to Increase Turbidity Removal in Raw Water - Ridwan, Ridwan; Afrianita, Reri; Kurniawan, Yogi (LPPM Universitas Andalas, 2021)
This study applies a new method to remove the turbidity of raw water in the sedimentation unit called CDF sedimentation using the working principle of a leaky tank at the bottom of the tank. The test was carried out on a laboratory scale reactor of 240 L/hour for 6 hours consisting of a waterfall coagulation unit for 5 seconds and alum as a coagulant. perforated wall flocculation unit with 30 minutes detention time and 1 hour CDF sedimentation unit. The study was conducted with 4 variations of CDF, namely 0%, 1%, 3%, and 5% with turbidity of 75.25 NTU. The results showed the greater the CDF value, the greater the decrease in turbidity that occurred. The highest level of turbidity removal occurred at 5% CDF value with an efficiency of 91,09%, a correlation value -0,927, and a significance value of 0,00 < 0,05. CDF value gives an influence on Reynolds numbers and Froude numbers in sedimentation units where Reynolds numbers are in the range 65,71-76,75 and Froude numbers 1,96x10-4-2,29x10-4. This shows the Reynolds number and the Froude number will get bigger as the value of the CDF and still matches the design criteria of the laminar. Keywords: The CDF sedimentation, Efficiency, and Turbidity.